(untitled) (Medico Legal Update, 2021)
Breast milk is really beneficial for baby’s nerves and brain system development so it can be optimal andit can decrease infection risk. This is not directly proportional with exclusive breastfeeding coverage score in Indonesia, which reached 42% and it is still below of WHO standard one of factors which affects the succeed of giving breast milk was an availability of counselor in Health Service Facility. The objective of the research is to know how deep the beneficial of breastfeeding counseling through 7 counselor contacts based on WHO standard onto mothers and family, especially in increasing breastfeeding coverage score. The research methodology used was quasi experiment. The subject of the research was pregnant women up to the phase of breastfeeding in Health Facility at the First Level in Tangerang. The used sampling technique was purposive sampling. The amount of sample was 30 mothers. The statistical analysis used was t-test paired test. The result shows that all of the samples who got treatment of having 7 counselor contacts reached 100% of breastfeeding until it last to the end. Meanwhile, t test result of counselor contacts with baby’s weight was having average differences of newly born baby’s weight and in the day 1-3, it was proved with significance score 0,000. The average score of baby’s weight who were newly born got 3, 16 kg and in the day of 1-3, got 3, 08kg, means decreased. However, for the t-test paired test, the baby’s weight in the day of 1-3, day of 7, day of 14 and day of 40, had average differences with significance score 0,000. The average score of baby’s weight in the day of 1-3, in the day of 7, in the day of 14, and in the day of 40 got increased. It can be concluded that the implementation of 7 counselor contacts of breastfeeding based on WHO standard was effective to increase exclusive breastfeeding coverage score and increase baby’s weight in Health Facility at the First Level. This research is supposed to be implemented in all of Health Facilities at the First Level, so the score of exclusive breastfeeding coverage increased.